Aplikasi Android Pengelolaan Informasi Kebersihan Keamanan Ketertiban Masyarakat di Lingkungan Kelurahan Setonogedong Kota Kediri - Agustono Heriadi; Dwi Nugroho; Dika Eko Prasetyo; Ratna Widyastuti (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The society of Setonogedong Village has carried out activities in order to maintain cleanliness, security and environmental order. The activities of maintaining cleanliness, security and environmental order are carried out through community cooperation. However, efforts to maintain cleanliness, security and environmental order have not been carried out optimally, this is proved by the existence of people who do not know about how to submit complaints about cleanliness, security and environmental order. This community service activity produces an e-government android application that is expected to help the community to convey information related to efforts to maintain cleanliness, security and environmental order in the Setonogedong Village, Kediri City.